2006
DOI: 10.1158/0008-5472.can-05-3138
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of the FoxM1 Transcription Factor Accelerate Development and Progression of Prostate Carcinomas in both TRAMP and LADY Transgenic Mice

Abstract: The proliferation-specific Forkhead Box M1 (FoxM1 or FoxM1b) transcription factor is overexpressed in a number of aggressive human carcinomas. Mouse hepatocytes deficient in FoxM1 fail to proliferate and are highly resistant to developing carcinogen-induced liver tumors. We previously developed a transgenic (TG) mouse line in which the ubiquitous Rosa26 promoter was used to drive expression of the human FoxM1b cDNA transgene in all mouse cell types. To investigate the role of FoxM1b in prostate cancer progress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
246
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(258 citation statements)
references
References 46 publications
12
246
0
Order By: Relevance
“…Consistent with the important role of Foxm1 in cell cycle progression, elevated Foxm1 levels have been found in a variety of tumor cell lines (Korver et al, 1997;Ye et al, 1997) as well as numerous types of human tumors (Teh et al, 2002;van den Boom et al, 2003;Lee et al, 2004;Obama et al, 2005;Wonsey and Follettie, 2005;Kalin et al, 2006). Our recent studies demonstrated that Foxm1 protein is abundantly expressed in highly proliferative human NSCLC as well as in mouse lung tumors induced by urethane (Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with the important role of Foxm1 in cell cycle progression, elevated Foxm1 levels have been found in a variety of tumor cell lines (Korver et al, 1997;Ye et al, 1997) as well as numerous types of human tumors (Teh et al, 2002;van den Boom et al, 2003;Lee et al, 2004;Obama et al, 2005;Wonsey and Follettie, 2005;Kalin et al, 2006). Our recent studies demonstrated that Foxm1 protein is abundantly expressed in highly proliferative human NSCLC as well as in mouse lung tumors induced by urethane (Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 71%
“…Our results provide novel and compelling evidence that FOXM1, a forkhead/winged-helix transcription factor that is specifically upregulated in a broad variety of cancers, that is, colon, prostate, pancreas and lung cancers (Pilarsky et al, 2004;Kalin et al, 2006;Yoshida et al, 2007), functions downstream of this cascade and is required for regulation of invasion and anchorage-independent growth. It is tempting to speculate that FOXM1 serves as one of the major relay stations for the induction of invasion by signals through the Ras-p38 pathway and that cellular phenotype decisions may in part depend on FOXM1.…”
Section: Introductionmentioning
confidence: 61%
“…FOXM1 is a forkhead/winged-helix transcription factor that is specifically upregulated in a broad variety of cancers, that is, colon, prostate, pancreas and lung cancers (Pilarsky et al, 2004;Kalin et al, 2006;Yoshida et al, 2007). Moreover, this transcription factor appears to play a major role in early tumorigenesis of head and neck squamous cell cancers (Gemenetzidis et al, 2009) and seems not to induce apoptosis (Kalinina et al, 2003;Gusarova et al, 2007;Park et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…FoxM1 has a critical function in G2 and M transition by regulating the expression of various G2/M cell cycle regulatory genes, including polo-like kinase, cyclin B, cyclin A, CDC25B and CDC2 (Wang et al, 2002a, b;Yoshida et al, 2007), and loss of FoxM is associated with G2/M checkpoint arrest and loss of mitotic spindle integrity (Laoukili et al, 2005;Wonsey and Follettie, 2005). Overexpression of FoxM1 through chromosomal amplification or the activation of transcription, for example, through Gli-1 is associated with the development and progression of many cancer types, including cancers of the breast, liver, prostate, brain and lung (Teh et al, 2002;Kalinichenko et al, 2004;Kalin et al, 2006;Kim et al, 2006;Liu et al, 2006;Madureira et al, 2006). Other mechanisms of interaction may exist between FoxM1 and FoxO3a.…”
Section: Foxo Transcriptional Network and Cell Cyclementioning
confidence: 99%